REGIONAL EFFECTS OF MONETARY POLICY IN INDONESIA - Rifai Afin (Trunojoyo University of Madura, 2007)
The main objective of this paper is to measure and interpret the dynamic effect of monetary policy on regional or provincial macroeconomic indicator such as Regional Gross Domestic Product and a response of Provincial Government as indicated by their Consumption. Regional economic differences may exist, making the implementation of monetary policy based on national averages controversial. We explore this possibility by measuring the impacts of monetary policy across province of Indonesia. Using regional VAR, we find differences in the effects of monetary shocks across province of the Republic of Indonesia. Our regional VAR suggest that aggregate VARs that ignore regional variations can suffer from severe aggregation bias. Impulse response functions from estimated regional VAR models reveal differences in policy responses. The size of a monetary response is significant related to regional economic activity.